The difference in physical activity and sedentary behavior during the COVID-19 pandemic in medical and non-medical students at Diponegoro University - Anwar, Rylandnia Sucha; Dieny, Fillah Fithra; Murbawani, Etisa Adi; Fitranti, Deny Yudi (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2023)
Background: University students are already known as a population at high risk for inactive behavior, and the COVID-19 pandemic can increase this risk. Objective: This research was conducted to analyze differences in physical activity and sedentary behavior during the COVID-19 pandemic in medical and non-medical students at Diponegoro University and analyze factors correlated to physical activity and sedentary behavior. Methods: This was an observational research with a cross-sectional design in two groups conducted online. The subjects were students of Diponegoro University, as many as 102 subjects (51 medical students and 51 non-medical students aged 18-22 years). The research was conducted from September to November 2021. The selection was by quota sampling technique. Data were collected by filling out Google forms and an interview. The dependent variables are physical activity and sedentary behavior, measured by the International Physical Activity Questionnaire-Long Form (IPAQ-LF) and the Adolescent Sedentary Activity Questionnaire (ASAQ). Data were analyzed by the Mann-Whitney test and Spearman's correlation test.Results: Physical activity during the COVID-19 pandemic between medical and non-medical students did not differ significantly (p=0.497). There was no significant difference in physical activity related to work/college, transport, house chores, and recreation (p>0.05). Meanwhile, overall sedentary behavior was not significantly different (p=0.290), as well as sedentary behavior on weekdays and weekends (p>0.05). The level of motivation was significantly correlated with physical activity in medical (p=0.027) and non-medical students (p=0.042).Conclusion: Medical and non-medical students have no differences in physical activity and sedentary behavior during the COVID-19 pandemic. The level of motivation was positively correlated to physical activity in medical and non-medical students.